ANALYSIS OF EMPLOYEE PERFORMANCE EVALUATION AT THE POPULATION AND CIVIL REGISTRATION OFFICE OF NORTH TORAJA REGENCY - Lambe, Kristian H P; Tandi, Asrin; Pangalo, Triswanti (Journal of Entrepreneur, Business and Management, 2023)
This study investigates employee performance at the Population and Civil Registration Office of North Toraja Regency, focusing on performance outcomes, inhibiting factors, and the effectiveness of employee performance. Performance is measured in terms of quality and quantity of work done according to set standards. The research identifies that employee performance at the office is generally good, with employees providing services according to established procedures. However, issues like delayed population document issuance due to incomplete data submission by the public and reliance on brokers hinder performance. The effectiveness of employee performance is deemed less effective, with a performance achievement rate of 83.33%, which is below the threshold for effectiveness as defined in the study.Keywords: Employee Performance, Pruductivity and Effectiveness